Extraction, characterization and application of phenolics from cinnamon barks and banana peels - Sirorat Jaisanti; Anal, Anil Kumar; Rakshit, Sudip Kumar; Athapol Noomhorm; Royal Thai Goverment Fellowships (Pathum Thani, Thailand : Asian Institute of Technology, 2010)
The basic aim of this study was to determine the phenolic contents and the effectiveness of banana peel and cinnamon extracts as an antioxidants. Thetwo methodswere used to extract the phenolic compounds from banana peel and cinnamon bark. One method was vacuum microwave method and another method was ultrasonic extraction. The two methods were combined with different temperature and time of extraction to discover the best method and favorable conditions for the effective extraction of phenolics from the studied samples. Moreover, this study was performed to analyze the effects of methods, extraction temperature and time on extraction yields and phenolic contents of banana peels and cinnamon barks. In addition, the characterizations of the antioxidant compounds of both samples were analyzed by determining flavonoid content, DPPH(2,2-Diphenyl-1-1picryhydrazyl)radical scavenging activity(%DPPH)and total antioxidant activity(TAA). The antioxidant activity was analyzed by measuring theoil oxidation rates after applyingof sample extracts into the commercial oils. Moreover, this study was performed to study the effects of concentrations, temperatures and time of storage on the antioxidant activity of sample extracts. Fish and canola oil were used as the substrate to examine the oxidation rate of oil. The peroxide value was measured as a parameter to indicate the degree of oxidation.There were three different concentrations (800, 1600, 2400 ppm) and two temperature levels(25oCand 55oC)of storage were identifiedto analyze the effects of concentration and temperature of two weeks storage forthe antioxidant activity. The experiment was done against the control (oil without extracts). In this study, it was found that the methods,extraction temperature and time affect the extraction yield and phenolic content of banana peel and cinnamon bark. The cinnamon bark extract (466.80 mg gallic acid/g extract)had much higher phenolic content than banana peel extract (35.06 mg gallic acid/gextract). The flavonoid content found in banana peel and cinnamon bark extracts were 196.05 and 427.91 mg/g, respectively. In addition, it wasfound that cinnamon gave higher %DPPH and TAA than banana peel extract. For the antioxidant activitystudy by applying the extracts into the commercial oil, the banana peel and cinnamon extract had shown the ability as antioxidant to prevent the oxidation of fish oil and canola oil. In addition, it was found that the different concentrations, temperatures (in these case are 25oCand 55oC ) and times affect the antioxidant activity. At lower concentration (800 ppm), the both extracts were higher effective in retarding the oxidation rates than higher concentration (1600 and 2400 ppm) for the oil kept at 25oC.
Submitted in partial fulfillment of the requirements for the degree of Master ofScience in Food Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2010
Keywords: Cinnamon